EFFECT OF FERTILIZER LEVELS ON YIELD ATTRIBUTING CHARACTERS OF RELAY CROPS IN RICE - KALITA, B. (Annals of Agricultural Research, 2014)
Field experiment was conducted at Instructional-cum-Research Farm, AssamAgricultural University, Jorhat. The experiment was laid out in factorial randomization block design with twelve treatment combination and three replications.The fertilizer doses was applied on relay crops at 50, 75, 100 and 125 per cent recommended levels of fertilizer for linseed, pea and khesari were 40-20-10, 20-40-10 and 20-40-10 N-P2O5- K2O kg/ha, respectively.The highest plant height,number of branch/plant at harvest and number if capsule or pod/plant was recorded at 125 per cent recommended levels of fertilizer.The highest plant height, number of branch/plant at harvest, number of capsule or pod/plant was recorded at 125 per cent recommended levels of fertilizer in all the relay crops .The highest available N, P and K was recorded at 125 per cent recommended levels offertilizer, which might be due to the incorporation of higher levels of more N enriched root mass of relay crops.